Observations and mechanisms of upwelling in the northern KwaZulu-Natal Bight, South Africa. (1st June 2016) - Roberts, MJ; Nieuwenhuys, C
Abstract : New in situ time-series data were acquired by two ADCP moorings placed on the shelf off Richards Bay on the east coast of South Africa at depths of 25 m and 582 m between October 2009 and August 2010. The 11-month inshore bottom-temperature record revealed five substantial upwelling events lasting 5–10 days each where temperatures decreased by about 7 °C to 17–18 °C. Satellite sea surface temperature data showed these events to coincide with cold-water plumes occupying the northern wedge of the KwaZulu-Natal (KZN) Bight. Numerous shorter duration (1–2 days) upwelling events with less vivid surface expressions were also observed throughout the entire record where bottom temperature dropped by 2–3 °C. The last four months of the record were characterised by a protracted cool period lacking a seasonal trend but punctuated with oscillations of warm and cooler bottom water. In contrast to earlier studies that suggested upwelling was topographically and dynamically driven by the juxtaposition of the Cape St Lucia offset and the Agulhas Current (a solitary mechanism), our analysis showed almost all major and minor cold-water intrusions to coincide with upwelling-favourable north-easterly winds that simultaneously force a south-westerly coastal current. Ekman veering in the bottom boundary layer of the Agulhas Current, and the concomitant movement of cold water up the slope, was found to coexist at times with coastal upwelling, but its absence did not impede inshore cold-water intrusions, calling into question its role as a primary driver of upwelling. Both major and minor upwelling events were observed to promote phytoplankton blooms in the northern KZN Bight which commonly extended to the Thukela River. Wind-driven upwelling was also observed in the inner bight between Richards Bay and Port Durnford, explaining the ribbon of coastal chlorophyll continuously observed on ocean colour images between Cape St Lucia and the Thukela River. Similarities in upwelling character and mechanisms are observed between the northern KZN Bight and the Florida Current shelf systems.